Cortical and cancellous bone in the human femoral neck: Evaluation of an interactive image analysis system - Bell, K; Garrahan, N; Kneissel, M; Loveridge, N; Grau, E; Stanton, M; Reeve, J (1996)
An interactive image analysis package was developed to examine whole cross-sections from the femoral neck. The package quantifies cortical width (Ct.Wi), cortical porosity (Ct.Po), and proportions of cortical, cancellous bone as a percentage of bone plus marrow area. Segmental analysis was used to quantify circumferential variations in bone distribution within the femoral cross-section. To evaluate reproducibility of data four independent operators analyzed previously prepared femoral neck sections from a 2000 BC population. Differences in total and circumferential distributions of cortical and cancellous bone with respect to gender and age of samples were demonstrated. Reproducibility was assessed using coefficients of variation (CV). Analysis of sections using a variable magnification, giving largest possible image size, rather than a set magnification reduced variation between operators for all measurements. Use of a calculated threshold significantly decreased variation between operators for the proportions of cortical and cancellous bone (p ≤ 0.026). Dividing the image into 8 rather than 16 segments also improved reproducibility. There was little agreement between operators in the determination of cortical porosity. The mean CV for the other quantitative indices such as cortical width and proportions of cortical and cancellous bone ranged from 4.87% to 13.52%. The genders showed similar patterns in circumferential distribution of bone. Cortical width was significantly greater in the inferior region compared to the other areas, whereas percent cortical bone was lowest at the superior region. The center of mass (COM) for the younger age group was located anteriorly, whereas in the older samples the COM was located posteriorly of the center of area (p = 0.041). Basic data relating to cortical and cancellous bone of acceptable reproducibility in comparison with current standards in iliac histomorphometry can now be pro-vided at modest cost in operator time and resources. © 1996 by Elsevier Science Inc.